1996
DOI: 10.1161/01.str.27.11.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of the Protein C System and Fibrinolysis in Infection-Associated Stroke

Abstract: Impairments in the protein C pathway and endogenous fibrinolysis may contribute to the increased risk for brain infarction after recent (< or = 1 week) infection/inflammation. A decrease in the circulating anticoagulant APC may be related to elevated antiphospholipid antibody titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 55 publications
0
77
0
1
Order By: Relevance
“…21,22 Thus, prior studies suggest that PC activation has important protective effects in both arterial thrombosis models and inflammatory-prothrombotic conditions, 23 processes synergistic in the pathogenesis of focal brain ischemia. 2,24 The procedure of carotid endarterectomy routinely includes heparin pretreatment and surgical carotid crossclamping, precautionary measures to inhibit thrombin generation and reduce risk of cerebral thromboembolism. Intraoperative neurological monitoring confirms that this procedure was well tolerated in those patients, which demonstrated increased IJ APC levels during carotid occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Thus, prior studies suggest that PC activation has important protective effects in both arterial thrombosis models and inflammatory-prothrombotic conditions, 23 processes synergistic in the pathogenesis of focal brain ischemia. 2,24 The procedure of carotid endarterectomy routinely includes heparin pretreatment and surgical carotid crossclamping, precautionary measures to inhibit thrombin generation and reduce risk of cerebral thromboembolism. Intraoperative neurological monitoring confirms that this procedure was well tolerated in those patients, which demonstrated increased IJ APC levels during carotid occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a deficiency in circulating APC is a distinct characteristic of the inflammatory-prothrombotic state following acute ischemic stroke. 2 Plasma from patients with ischemic stroke also exhibits reduced anticoagulant response to exogenously added APC that is not attributable to the factor V Leiden mutation. 35,36 These findings, along with recent controversy regarding thrombolytic therapy, highlight a need for further studies investigating potential cerebral protective effects of endogenous or therapeutically administered APC in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3,5,15,18,22,23,51,62,79,80,84,100,101] These changes can be found from a few minutes up to 2 weeks after the onset of brain ischemia. It is not clear, however, whether these hemostatic abnormalities precede or follow the neurological event.…”
Section: Hemostatic Theorymentioning
confidence: 99%
“…[23] It has also been shown that stroke patients have lower levels of circulating APC compared with control patients and community control subjects. [79] Because protein C antigen and APC levels were not measured before the stroke in these studies, it is difficult to say whether observed reductions preceded or followed the neurological event.…”
Section: Antithrombotic Mechanismsmentioning
confidence: 99%